Program pelatihan pembuatan Nugget Lele: Peningkatan keterampilan Ibu-Ibu Posyandu Dusun Citro Dukuh dalam upaya pencegahan stunting - Ariyanti, Efi; Septina, Berlian Ayu (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Nutrition plays a vital role in the human life cycle. Malnutrition in infants and toddlers can hinder their growth and development, which, if not addressed, can continue into adulthood, preventing them from reaching optimal potential. Therefore, it is essential to provide quality complementary breast milk (MP-ASI) from 6 months to 24 months while continuing to provide breast milk until 24 months or more. Insufficient nutritional intake during the first 1000 days of life can cause stunting, a condition where a child has a height below WHO growth standards. In Citro Hamlet, several stunted toddlers were found. To overcome this problem, UIN Salatiga students suggested an intervention in the form of training in making catfish nuggets, which are a source of high-quality protein and other essential nutrients. The method used during implementation involved a socialization approach, training, and a demonstration of making catfish nuggets. The activity succeeded in improving the skills of Posyandu participants in preventing stunting. This training also helps mothers provide unique forms of food that children like.